CONFIRMATORY FACTOR ANALYSIS TO KNOW THE INFLUENCING FACTORS OF ELEMENTARY SCHOOL STUDENTS’ SELF-CONCEPT IN JETIS SUB DISTRICT, BANTUL REGENCY - Firmansyah Firmansyah; Rozanah Katrina Herda; Angga Damayanto; Fajar Sidik (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2020)
This research aimed to know the factors that influenced elementary students’ self-concept in Jetis Sub District, Bantul Regency, Yogyakarta. The subject of this research consisted of 200 fourth grade students from four different elementary schools in Jetis Sub District. The result showed the fit model with one dimension. The value of each fit parameter of GFI, RMSEA, NFI, IFI, CFI, TLI, and AGFI was 0.958, 0.066, 0.953, 0.976, 0.976, 0.967, and 0.958. All factors or dimensions in self-concept instrument had good reliability by looking at the value of CR ≥ 0,7 categorizing as good reliability, while the value between 0,6 and 0,7 considered to acceptable reliability by underlining that the indicator has load factor that matched the criteria. The internal consistency could be measured by using Average Variance Extracted (AVE). The AVE value that was recommended was ≥ 0,5. This clearly showed that self-concept has validity evidence of internal structure. Moreover, self-concept has convergent and discriminant validity. The self-concept reliability was considered good, so it will give a relatively consistent result when there is re-measurement.